2019
DOI: 10.3389/fgene.2019.00373
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potential Crucial Genes Associated With the Pathogenesis and Prognosis of Endometrial Cancer

Abstract: Background and Objective: Endometrial cancer (EC) is a common gynecological malignancy worldwide. Despite advances in the development of strategies for treating EC, prognosis of the disease remains unsatisfactory, especially for advanced EC. The aim of this study was to identify novel genes that can be used as potential biomarkers for identifying the prognosis of EC and to construct a novel risk stratification using these genes. Methods and Results: An mRNA sequencing dataset, corresponding survival data and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 94 publications
6
54
0
Order By: Relevance
“…After co-expression and correlation analysis using the Oncomine, bc-GenExMiner, and UCSC Xena web-based tools in the present study, we confirmed that CDC20 gene was positively correlated with BIRC5 expression. As a matter of fact, both CDC20 and BIRC5 were found to be co-expressed in lung adenocarcinoma, endometrial cancer, renal cell carcinoma, and thyroid carcinoma [31][32][33][34]. Given that cell cycle process is often coordinated with apoptotic proteins to maintain tissue homeostasis, silencing the expressions of cell cycle protein as well as anti-apoptotic proteins simultaneously could potentially lead to cell cycle arrest and reduce the proliferation of breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…After co-expression and correlation analysis using the Oncomine, bc-GenExMiner, and UCSC Xena web-based tools in the present study, we confirmed that CDC20 gene was positively correlated with BIRC5 expression. As a matter of fact, both CDC20 and BIRC5 were found to be co-expressed in lung adenocarcinoma, endometrial cancer, renal cell carcinoma, and thyroid carcinoma [31][32][33][34]. Given that cell cycle process is often coordinated with apoptotic proteins to maintain tissue homeostasis, silencing the expressions of cell cycle protein as well as anti-apoptotic proteins simultaneously could potentially lead to cell cycle arrest and reduce the proliferation of breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al found that ESPL1 may be associated with bladder cancer development and recurrence [33]. In addition, Liu et al identi ed 7 pivotal genes involved in endometrial cancer prognosis and constructed a prognostic gene signature, among which ESPL1 was one of the genes that were viewed as risky prognostic genes [34]. ESPL1 expression was found to be increased in endometrial cancer tissues, but the clinical signi cance and functional mechanism of ESPL1 in EC remains to be veri ed [34].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Liu et al identi ed 7 pivotal genes involved in endometrial cancer prognosis and constructed a prognostic gene signature, among which ESPL1 was one of the genes that were viewed as risky prognostic genes [34]. ESPL1 expression was found to be increased in endometrial cancer tissues, but the clinical signi cance and functional mechanism of ESPL1 in EC remains to be veri ed [34]. Nevertheless, it has also been reported that ESPL1 plays an opposite role in gastric adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…The DNA topoisomerase 2-alpha (TOP2A) is involved in the cell cycle, and it is crucial to cancer development as indicated by its expression, described as upregulated in several types of cancer, including pancreatic cancer [60,61]. Network analyses identified TOP2A among the hub proteins in the protein-protein interaction network in glioblastoma, rectal adenocarcinoma, and endometrial cancer [60][61][62]. In pancreatic cancer, TOP2A is associated with tumor size, metastasis, tumor stage, poor prognosis.…”
Section: Discussionmentioning
confidence: 99%